Етнолінгвістична характеристика українських фразеологізмів з архетипом земля - Грозян, Н.Ф.; Кадырова, А.Д. (Культура народов Причерноморья, 2013)
У статті подається етнолінгвістична характеристика фразеологічних одиниць з архетипом земля. З’ясовано, що архетип земля характеризується винятковими можливостями включатися в різноманітні контексти та утворювати стійкі звороти. Фразеологічні одиниці з компонентом земля характеризуються етнолінгвістичною різноманітністю, значним конотативним потенціалом, передають дух нашої давнини. Виявлено, що фразеологізми з компонентом земля відображають тісний зв’язок українського народу з землею, яка сприймається не лише в прямому значенні як ґрунт, а значно ширше – як першооснова буття. В статье представлена этнолингвистическая характеристика фразеологических единиц с архетипом земля. Выявлено, что архетип земля характеризуется исключительными возможностями включаться в различные контексты и образовывать устойчивые обороты. Фразеологические единицы с компонентом земля характеризуются этнолингвистическом разнообразием, значительным конотативним потенциалом, передают дух нашей древности. Обнаружено, что фразеологизмы с компонентом земля отображают тесную связь украинского народа с землей, воспринимаются не только в прямом смысле как почва, а значительно шире – как первооснова бытия. The article deals with the ethno-linguistic characteristics of phraseological units with the archetype ‘the land’. It was identified that they are characterized by ethno-linguistic variety and significant connotative potential. The purpose of the article is to identify the ways of displaying the ethno-cultural information in the phraseological units with the archetype ‘the land’. Analyzing phraseological units with the archetype ‘the land’ we can distinguish them into several groups with the following symbolic meanings: the land - nurse, the land - mother, the land - sacred, the land - the birthplace, the land - the basis of wealth, and the land as the tomb. It was revealed that the archetype ‘the land’ was characterized by exceptional feature of being included in different contexts. It was found that the attachment to the land was one of the major features of the Ukrainian national ideology. It was proved that the image of ‘the land as the nurse’ was glorified on ethnic Ukraine for centuries. The phraseological units with the archetype ‘the land’ capture the spirit of our ancient times, it also captures the close relationship of the Ukrainian people with the land, which is seen not as the soil in literary sense, but much more - as a fundamental principle of life that helps to understand the depth of the Ukrainian soul.